2019
DOI: 10.1186/s42358-019-0072-x
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD69+ T cells and CD4+CD25+FoxP3+ Treg cells imbalance in peripheral blood, spleen and peritoneal lavage from pristane-induced systemic lupus erythematosus (SLE) mice

Abstract: Background: Adaptive immune cells, including CD4 + CD69 + and CD4 + CD25 + FoxP3 + regulatory T (Treg) cells, are important for maintaining immunological tolerance. In human systemic lupus erythematosus (SLE), CD4 + CD25 + FoxP3 + Treg cells are reduced, whereas CD69 expression is increased, resulting in a homeostatic immune imbalance that may intensify autoreactive T cell activity. To analyze the mechanisms implicated in autotolerance failure, we evaluated CD4 + CD69 + and CD4 + CD25 + FoxP3 + T cells and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…Furthermore, it seems that the reduction of IFNγ explains the increase in FOXP3 mRNA expression rather strongly, as shown by the R 2 value of 0.616 (p=0.001). The above result was consistent with several studies in pristane induced models; a decrease in FOXP3+ T-cells and increase in CD4+CD69+ T-cells coincide with an increase in IFNγ levels in intraperitoneal fluid 20 , 23 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, it seems that the reduction of IFNγ explains the increase in FOXP3 mRNA expression rather strongly, as shown by the R 2 value of 0.616 (p=0.001). The above result was consistent with several studies in pristane induced models; a decrease in FOXP3+ T-cells and increase in CD4+CD69+ T-cells coincide with an increase in IFNγ levels in intraperitoneal fluid 20 , 23 .…”
Section: Discussionsupporting
confidence: 93%
“…The expression of FOXP3 mRNA in pristane induced murine models is a marker for Treg cell activity. In a study by Peixoto et al ., it was shown that on day 90 and 120 post induction there was a decrease in CD4+CD25+FOXP3+ (Treg) cell count in peripheral blood samples 20 . These authors also showed that the reduction in Treg count was correlated with an increase in IFNγ (p=0.017), TNFα (p=0.043) and TGF-β1 (p=0.038).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we showed that 17β-estradiol treatment increased the expression of early activation marker CD69 and IFNγ on CD3 + T cells ( Figure 7 ). Others have shown increased numbers of CD4 + CD69 + T cells with altered expression of interleukins and suggested a correlation with loss of self-tolerance in lupus mice ( 61 ). Of clinical significance, a human study in lupus patients also found that CD69 + T cells are increased and defective in function ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…As both immunosuppressive CD4 + -Tregs and stimulating CD4 + -Tresps are involved [13,15,33,34], it seems likely that a misguided differentiation of either CD4 + -Tregs or CD4 + -Tresps or probably of both CD4 + -T-cell subsets causes an imbalance in the ratio of CD4 + -Tregs to CD4 + -Tresps in these patients. This balance has been intensively studied in recent years, providing contradictory results, and was shown to depend on the selection of the respective Treg/Tresp subsets [35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%